Influence of environmental loading on the tensile and cracking behaviour of textile reinforced cementitious composites. (30th August 2018) - De Munck, M.; El Kadi, M.; Tsangouri, E.; Vervloet, J.; Verbruggen, S.; Wastiels, J.; Tysmans, T.; Remy, O.
Highlights: Compared to freeze-thaw cycles, heat-rain cycles cause a larger degradation of the mechanical properties. Hydration of unreacted cement particles during heat-rain cycles leads to further strength development. The stress level at which cracks are formed diminishes after being subjected to environmental loading. Abstract: In outdoor applications, textile reinforced cementitious composites (TRCs) are susceptible to varying weathering conditions. To guarantee their performance during the entire life-time, it is necessary to evaluate the long-term behaviour. In this paper, the mechanical behaviour of reference specimens is compared to aged specimens, which are subjected to heat-rain and/or freeze-thaw cycles. Results show that subjection to heat-rain cycles leads to a larger degradation of the tensile behaviour compared to subjection to freeze-thaw cycles. Besides the macroscopic tensile behaviour, also the cracking behaviour is evaluated. Analysis shows that cracks are formed at lower stress levels after being subjected to environmental loading.